Targeting Cdc42 in cancer. (November 2013) - Arias-Romero, Luis E; Chernoff, Jonathan
<x xml:space="preserve">Abstract</x> Introduction: The Rho GTPases are a family of proteins that control fundamental cellular processes in response to extracellular stimuli and internal programs. Rho GTPases function as molecular switches in which the GTP-bound proteins are active and GDP-bound proteins are inactive. This article will focus on one Rho family member, Cdc42, which is overexpressed in a number of human cancers, and which might provide new therapeutic targets in malignancies. Areas covered: In this article, the key regulators and effectors of Cdc42 and their molecular alterations are described. The complex interactions between the signaling cascades regulated by Cdc42 are also analyzed. Expert opinion: While mutations in Cdc42 have not been reported in human cancer, aberrant expression of Cdc42 has been reported in a variety of tumor types and in some instances has been correlated with poor prognosis. Recently, it has been shown that Cdc42 activation by oncogenic Ras is crucial for Ras-mediated tumorigenesis, suggesting that targeting Cdc42 or its effectors might be useful in tumors harboring activating Ras mutations.